Communication Patterns of Child Protection Agency (LPA) Mataram City in Assisting Broken Home Family Conflicts - Darmayanti, Reni; Rahmawati, Endang; Ishanan, Ishanan (Jurnal Ilmiah Ilmu Sosial, 2025)
This research aims to analyse the communication patterns applied by the Child Protection Agency (LPA) of Mataram City in handling broken home family conflicts, especially those affecting children who are victims of physical, emotional, and neglect violence. Mataram City was chosen as the research location due to the high prevalence of divorce, domestic violence, and child neglect cases during 2022-2024. This research used a qualitative approach with a case study method. Data were collected through in-depth interviews, direct observation, and documentation studies, then analysed using the Miles and Huberman interactive model through the stages of reduction, presentation, and conclusion drawing. The results showed that the effective communication pattern applied by LPA (Child Protection Agency) Mataram City includes a trauma-informed care approach, the use of non-verbal communication media such as drawing and writing, and empathy-based counselling. This pattern contributes positively to children's psychosocial recovery, despite challenges such as a lack of empathic communication training and weak inter-agency coordination. Recommendations include strengthening the referral system between the Mataram City Child Protection Agency (LPA), schools and safe houses; developing an empathic communication training module based on local culture for field officers; and establishing a child protection policy coordination forum that is responsive to the dynamics of broken home families in urban areas.